MEMBIDIK PELUANG USAHA YANG TEPAT BAGI GENERASI MILENIAL - Pipin Sukandi; Yelli Eka Sumadhinata; Ayuningtyas Yuli Hapsari; Gallang Perdhana Dalimunthe; Annisa Lisdayanti; Irma Nilasari (Jurnal Abdimas Bina Bangsa, 2024)
Currently, many young people or better known as the millennial generation are entering the business world. Various fields are involved ranging from fashion, home furnishings to culinary businesses. But after they entered the business world, many felt inadequate because their business did not run even to bankruptcy. This is due to lack of knowledge about selling techniques. Not only good and cheap goods, but communication techniques, both verbal and non-verbal, are needed in the business world to attract consumers. This community service activity provides training on communication techniques, especially in the business world